Application of qualitative tests for detection of adulterants in pasteurized milk and during its subsequent storage - Aparnathi, K D; Agnihotri, Arpita; Chauhan, M P; Shaikh, A I; Patel, S I (Indian Journal of Dairy Science, 2019)
Effect of widely used heat treatments of milk on performance of selected qualitative tests for detection of common adulterants in the milk was carried out. Genuine and adulterated samples of milk were heated to 72°C for 16 sec for pasteurization. The samples of pasteurized milk were stored at temperature of 5±1ºC. The qualitative tests were performed for detection of adulterants at an interval of 24 hours. The performance of the qualitative tests varied depending on type of heat treatment employed in processing of milk, length of storage period for which samples were stored and chemical nature of the target adulterant spiked in the milk.